I suspect this is supposed to be done by using a^3+b^3+c^33abc = (a+b+c)(a+bw+cw^2) (a+bw^2+cw) where w is the complex cube root of unity (1+isqrt(3))/2  hence 'Complex'. But I used this method, more or less following earlier posts.
A = sum from 1 to infinity x^(3n3)/(3n3)! = (1/3 e^(x/2) (e^((3x)/2) + 2 cos((sqrt(3)x)/2)))
B = sum from 1 to infinity x^(3n2)/(3n2)! = (1/3 e^(x/2) (e^((3x)/2)  2 sin(1/6(π  3 sqrt(3)x))))
C = sum from 1 to infinity x^(3n1)/(3n1)! = (1/3 e^(x/2) (e^((3x)/2)  2 sin(1/6 (3 sqrt(3) x + π)))) and indeed when added these are the same as sum from 1 to infinity x^(n1)/(n1)! = e^x.
Now we have A^3+B^3+C^3 = 1/9 (e^(3 x) + 2 e^((3 x)/2) cos((3 sqrt(3) x)/2) + 6) and 3ABC = 1/9 (e^(3 x)  2 e^((3 x)/2) cos((3 sqrt(3) x)/2) + 3).
When added these cancel nicely to produce the number 9/9, or 1, which is the required value.
Edited on January 17, 2019, 7:13 am

Posted by broll
on 20190117 07:05:37 